Assessment of the Quality of Life of African Black Children with Atopic Dermatitis by the CDLQI Score - Yao Isidore Kouassi; K. C. Ahogo; O. F. Bia; K. A. Kouassi; H. S. Kourouma; A. S. Allou; K. P. Gbandama; K. Kassi; E. J. Ecra; M. Kaloga; I. P. Gbery; K. Kouamé; et al. (Sociedade Portuguesa de Dermatologia e Venereologia, 2021)
Introduction: Atopic dermatitis (AD) is a chronic inflammatory disease that affects both children and adults. The main symptom is pruritus, which has an important impact on quality of life (QoL). The objective of our study was to assess the impact of AD on the quality of life of children through the CDLQI score. Population and Methods: We performed a cross-sectional survey, with descriptive and analytical aims, carried out on the basis of prospective recruitment, carried out over a period of 7 months from December 2017 to June 2018. The study included children (5-16 years) with AD selected during dermatology consultations at the Centre Hospitalier Universitaire of Treichville. Data collected included the socio-demographic characteristics of patients and their AD and the results of a questionnaire on the severity score (SCORAD) and the quality of life index in these children (CDLQI). Results: We included 60 children, mainly within the group from 05 to 09 years (57%). CDLQI average score was 9.9 and mean SCORAD 24. Pruritus, insomnia and sadness had more impact on QoL. We found a strong association between the severity of AD objectified by SCORAD and the CDLQI. Conclusion: The study reveals a high impact of AD on the QoL of children in Abidjan mainly through pruritus, insomnia and sadness. It opens up reflection on the need for education for AD management and the prospect of creating an atopy school in Côte d'Ivoire.